2019
DOI: 10.6004/jnccn.2018.7103
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Locoregional Recurrence After Failure to Achieve Pathologic Complete Response to Neoadjuvant Chemotherapy in Triple-Negative Breast Cancer

Abstract: Background: This study evaluated factors predictive of locoregional recurrence (LRR) in women with triple-negative breast cancer (TNBC) treated with neoadjuvant chemotherapy who do not experience pathologic complete response (pCR). Methods: This is a single-institution retrospective review of women with TNBC treated with neoadjuvant chemotherapy, surgery, and radiation therapy in 2000 through 2013. LRR was estimated between patients with and without pCR using the Kaplan-Meier method. Patient-, tumor-, and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Apart from the predictive and prognostic factors known to date, including staging, grading, HER2 status, hormone receptors status, and Ki 67%, the therapeutic response of the tumour to NACT provides information about the patient's prognosis. Obtaining complete pathological response (pCR) de ned as ypT0/Tis, ypN0 translates into better EFS and OS [22,23,24,25,26]. This served as the basis for the US Food and Drug Administration in July 2020 to accept pCR as the nal point of clinical studies in the neoadjuvant therapy of early breast cancer with a high recurrence risk [23].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the predictive and prognostic factors known to date, including staging, grading, HER2 status, hormone receptors status, and Ki 67%, the therapeutic response of the tumour to NACT provides information about the patient's prognosis. Obtaining complete pathological response (pCR) de ned as ypT0/Tis, ypN0 translates into better EFS and OS [22,23,24,25,26]. This served as the basis for the US Food and Drug Administration in July 2020 to accept pCR as the nal point of clinical studies in the neoadjuvant therapy of early breast cancer with a high recurrence risk [23].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 109 patients were included in this study (Figure 1). All 109 included patients underwent NAC every 21 days [mean number of cycles: 4 (range, [3][4][5][6][7][8]]. The majority (90.8%) received an anthracycline plus taxane regimen.…”
Section: Patients and Treatmentsmentioning
confidence: 99%
“…A major advantage of this strategy is the ability to observe the tumor response to chemotherapy regimens before surgery ( 2 ). Patients with TNBC who achieve pathological complete response (pCR) after NAC have better prognosis than those who do not reach pCR ( 3 , 4 ); however, numerous patients with TNBC have residual disease (RD) after NAC, which is associated with a higher risk of relapse and distant metastasis ( 5 , 6 ). Novel prognostic biomarkers that can stratify these patients will be valuable for making individualized treatment decisions and maximizing therapeutic efficacy in specific patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [110] reported an association between post-NACT LVI and poor PFS (progression-free survival) as well as OS ( p < 0.91, respectively). Evidently, TNBC patients with LVI harbored residual cancer after NACT and were at significantly higher risk of LRR ( p < 0.001) [111]. The LVI situation is associated with many other clinical and pathological characteristics, including HR status, number of involved lymph nodes, and residual disease burden [112113].…”
Section: Analysis Of Post-nact Lymph Node Ratio (Lnr) Tumor-node-metmentioning
confidence: 99%